Saberes da tradição e a percepção ambiental dos moradores da comunidade rural de Chã da Pia, Areia-PB - Campos, Darnley Dias (2022)
Residents of the traditional rural community of Chã da Pia, Areia-PB, often do not feel valued for being artisans. Some are having to direct a different future for their children. That said, we cannot allow a traditional millenary culture to be lost in time and neither this traditional millenary knowledge, because the traditional millenary culture dies, part of our identity will also die. This made me anxious to carry out this study. This research was developed in the traditional rural community of Chã da Pia, northwest of the municipality of Areia-PB. The general objective of this work is to research, from a socio-environmental perspective, the traditional knowledge of the residents of Chã da Pia/Areia/PB, analyzing their environmental perception in the production of crockery and utensils made manually with clay and during the practice of subsistence culture developed by the residents of the locality. The specific objectives are: To identify aspects of environmental perception among the residents of the community of Chã da Pia, in their work; Analyze how traditional knowledge is taught from generation to generation among people in the community; Develop a plan of ecological trails to visit the “Quintais da Chã da Pia”, with the aim of reinforcing the tradition among the residents of the community. This research has an ethnographic, descriptive qualitative approach, as it is more adequate to understand the nature of a social phenomenon. The phases of this research were developed in hybrid mode. Data collection took place online, through WhatsApp and Google Meet, with interviews and application of semi-structured questionnaires to participants. The collected data were allocated to the Microsoft Office Excel 2016 platform, and were analyzed according to content analysis. Between the 10-year interval (2004 - 2014), there was a decrease in active artisans. In addition to the activity with clay, 57.1% practice subsistence agriculture, with maize and bean cultivars. When teaching traditional knowledge to other people, 5 answered yes and maybe they would teach that. The knowledge of tradition is passed on from the older to the younger ones through orally and experimentally from generation to generation, through tradition. The data show that only women pass on this knowledge: mother, sister and grandmother. The predominant environmental perception among the participants is anthropocentric, with 71.4% of them. In the stages of production of clay tableware, there is a very strong and evident gender issue. The research I conducted is not random, by the way. This dissertation is for and for the residents of the rural community to feel respected and valued as the righteous human beings that they are. This serves as an instrument for valuing the local millenary culture and the residents of the community. It is important both for Science and for the traditional rural community of Chã da Pia (or Pia) and the culture of Paraíba, perhaps the Northeast.